ANALISIS PENGARUH INFLASI DAN PERTUMBUHAN BIAYA PRODUKSI TERHADAP PROFIT MARGIN PADA PERUSAHAAN FOOD AND BEVERAGES YANG GO PUBLIK DI BEI - Nurkholifah, Siti; Abdullah, Muhammad Faisyal (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2010)
Inflation and Growth in the company's profit margin than Food and Beverages. Analysis tools used in this study is panel data regression, a combination of two data time series and cross section can provide more data so that it will generate degree of freedom (df) is greater, to determine the effect between inflation and growth in production cost profit margin ratio. Based on the conclusion, it can be concluded that the rate of inflation and growth in production costs affect the level of corporate profit margins at the Food and Beverages during the period 2005-2008 with a coefficient of determination equal to 96.83%. Partially between the inflation rate did not negatively affect the profit margin between the rate of inflation while the growth rate positively affects the production cost. So that can be implicated to obtain a high level of profit margin, then for company management to pay more attention to the level of growth in production costs, such as looking for suppliers who provide raw material prices are much cheaper so that more efficient control of production costs.